Exploratory Study on Concrete Tensile Strength with Varying Lengths of Nylon Strings - Mohamed Amin, Muhammad Idlan Haris; Yeoh, David Eng Chuan (Recent Trends in Civil Engineering and Built Environment, 2025)
The study aims to develop nylon-fiber-reinforced concrete by adding 2% per unit volume of 0.16 mm diameter nylon fibers to concrete. It investigates the impact of varying nylon fiber lengths (0 mm, 25 mm, 50 mm, and 75 mm) on the tensile strength of the concrete. The tensile and compressive strengths were measured after a 28-day curing period. Results showed that concrete with 25 mm fiber length exhibited the highest tensile strength (1.21 MPa), 1.09 times stronger than ordinary concrete. The compressive strength of the 25 mm nylon concrete was also higher (32.43 MPa) than the control samples. Despite meeting C25 concrete specifications, the study suggests further research on the impact of fiber length and diameter, as well as exploring bending, flexural strength, and other factors for a more comprehensive understanding.